2016
DOI: 10.1111/ddi.12443
|View full text |Cite
|
Sign up to set email alerts
|

The marine ‘great wall’ of China: local‐ and broad‐scale ecological impacts of coastal infrastructure on intertidal macrobenthic communities

Abstract: Aim Increasing areas of artificial infrastructure are being built along coastlines for purposes of land reclamation and coastal defences. Impacts of these structures on intertidal communities could be severe. Here, we tested the hypothesis that artificial structures can alter intertidal community composition by providing hard substrata for rocky intertidal species, and can serve as 'stepping stones' that facilitate broad-scale migration of rocky intertidal species and may weaken a phylogeographic transition.Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 74 publications
0
53
2
Order By: Relevance
“…We found that about ~9% of the coastline is made up of hard artificial structures, which are interspersed among sandy and rocky habitats (see Supporting Information Figure S6). Previous studies have shown that artificial infrastructures like breakwaters can reduce distances between populations and serve as “stepping‐stones” for the dispersal of rocky intertidal species with limited dispersal capacity (Dong, Huang, Wang, Li, & Wang, ; Firth et al., ). Scurria viridula commonly uses artificial breakwaters and seawalls as habitat, especially in highly urbanized coasts such as in central Chile (M.A.…”
Section: Discussionmentioning
confidence: 99%
“…We found that about ~9% of the coastline is made up of hard artificial structures, which are interspersed among sandy and rocky habitats (see Supporting Information Figure S6). Previous studies have shown that artificial infrastructures like breakwaters can reduce distances between populations and serve as “stepping‐stones” for the dispersal of rocky intertidal species with limited dispersal capacity (Dong, Huang, Wang, Li, & Wang, ; Firth et al., ). Scurria viridula commonly uses artificial breakwaters and seawalls as habitat, especially in highly urbanized coasts such as in central Chile (M.A.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the other eight cases of category III, the CDW is presumed to have acted as a contemporary barrier that limits the distribution of the newly derived haplotypes, and is responsible for the observed population structure. Larval tolerance to salinity (e.g., Han, Zhu, et al., ) and habitat discontinuity across the estuary (e.g., Dong, Huang, Wang, Li, & Wang, ; Dong et al., ), and sometimes the combined effects of these two factors (Ni, Li, Ni, et al., ), are thought to be the major influential mechanisms.…”
Section: Studies Claiming the Cdw Is A Barrier: All That Glitters Is mentioning
confidence: 99%
“…The conspicuous star‐shaped shell and large sizes that P. ferruginea can reach (>10 cm in diameter; see Espinosa & Rivera‐Ingraham, ) has made this species the target of human collection since the Quaternary (Espinosa, Rivera‐Ingraham, Fa, & García‐Gómez, ), being commonly used as food, bait for fishing, or for decorative purposes. In addition, the urban development of coastal areas has dramatically fragmented its habitat, leading to the alteration of local communities (Airoldi et al, ; Dong, Huang, Wang, Li, & Wang, ; Firth et al, ). Consequently, its distribution range has progressively contracted (Espinosa et al, ), with P. ferruginea nearly completely disappearing from European coasts, with the exception of the small populations present in Andalusia (Southern Spain), Corsica, and Sardinia (Espinosa et al, ).…”
Section: Introductionmentioning
confidence: 99%